Bile salts and derivatives: Rigid unconventional amphiphiles as dispersants, carriers and superstructure building blocks. Issue 3 (June 2015) - Galantini, Luciano; di Gregorio, M. Chiara; Gubitosi, Marta; Travaglini, Leana; Tato, José Vázquez; Jover, Aida; Meijide, Francisco; Soto Tellini, Victor H.; Pavel, Nicolae V.
Abstract Steroidal surfactants like bile salts have a rigid amphiphilic structure significantly different from the typical head–tail one. As a result, these molecules show peculiar features in their self-assembly behavior and solubilization and permeation abilities. Bile salts are widely used as starting materials in the preparation of synthetic derivatives by changing their amphiphilic structure and by introducing specific functionalities. Due to the steroid rigidity and the peculiar distribution of hydrophobic and hydrophilic domains, these molecules self-organize in ordered supramolecular assemblies and are particularly attractive for the bottom up construction of complex nanostructures. They often self-assemble in 1D structures such as tubes or fibers and show low molecular weight gelator features. Their tubular nanoscale structures have cross section diameters spanning a wide range of values (inner diameter 3–450 nm) and are sometimes formed through appealing pH or temperature responsive aggregations. Moreover, mixtures of these surfactants allow in some cases the preparation of mixed tubes with tunable composition and related features such as charge and sizes. The unconventional amphiphilic molecular structure of BSs dictates also remarkable abilities as carriers across tissues and membranes of many compounds (e.g. drugs, carbohydrates and ions). Therefore they are often employed as encapsulators, dispersants and transporters in complex systems. Chemical modifications can also be used to provide derivatives with improved performances.